Cochrane's Linked Data Project: How it Can Advance our Understanding of Surrogate Endpoints. Issue 3 (September 2019) - Mavergames, Chris; Beecher, Deirdre; Becker, Lorne A.; Last, A.; Ali, A.
Cochrane has developed a linked data infrastructure to make the evidence and data from its rich repositories more discoverable to facilitate evidence-based health decision-making. These annotated resources can enhance the study and understanding of biomarkers and surrogate endpoints.